1993
DOI: 10.1007/bf00175685
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis with teicoplanin in patients undergoing breast reconstruction with the transverse rectus abdominis myocutaneous flap

Abstract: The authors report the results of a randomized clinical trial of antibiotic prophylaxis for post-operative infection following breast reconstruction with the transverse rectus abdominis myocutaneous (TRAM) flap. The aim was to evaluate the efficacy and tolerability of short-term parenteral prophylaxis with teicoplanin; the endpoint of the study was the reduction of wound contamination assessed by microbiologic culture of drain fluid. From October 1990 to March 1992, 38 patients were recruited: 20 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Antrum, 1990 113 Interim analysis of Kester, 1999 23 Antrum, 1992 114 Interim analysis of Kester, 1999 23 Barlas, 1993 115 CCT but not assessing a glycopeptide (full paper was ordered as no abstract was available) Bayston, 1990 116 Not adult participants only Bell, 1990 117 Not a CCT (case series: full paper was ordered as no abstract was available) Brooks, 2002 118 Not a CCT (prospective cohort study) Bucknell, 2000 119 CCT but not assessing a glycopeptide (only MRSA high-risk patients received a glycopeptide) Cone, 2004 120 Duplicate of Mastronardi, 2004 121 Dazzi, 1994 122 Comparator not an alternative antibiotic regimen de Lalla, 2000 123 Comparator not an alternative antibiotic regimen de Lalla, 2001 124 Discussion paper (full paper was ordered as no abstract was available) De Lucas-Villarrubia, 2004 125 Not a CCT (prospective cohort study) Exner, 1992 126 Not a CCT (prospective cohort study) Ferro, 1997 127 Comparator not an alternative antibiotic regimen Feys, 1997 128 Comparator not an alternative antibiotic regimen Fontanesi, 1991 129 Discussion paper (full paper was ordered as no abstract was available) Franchelli, 1993 130 Comparator not an alternative antibiotic regimen Friberg, 1990 131 Not a CCT (case reports: full paper was ordered as no abstract was available) Gadallah, 2000 132 Not adult participants only. Primary outcome was peritonitis, SSIs were excluded from the analysis Haines, 1993 133 Letter Isringhaus, 1992 134 Not a CCT (pharmacokinetic study: all patients received same dose of glycopeptide) Karran, 1992 135 Comparator not an alternative antibiotic regimen Lazzarini, 2001 136 Not a CCT (prospective cohort) Lazzarini, 2003 137 Does not report a primary outcome (primary outcome is blood drug concentration) Mastronardi, 2004 121 Not a CCT (retrospective cohort) Mendivil Soto, 2001 138 Does not report a primary outcome Mini, 1999…”
Section: Presentation Of Resultsmentioning
confidence: 99%
“…Antrum, 1990 113 Interim analysis of Kester, 1999 23 Antrum, 1992 114 Interim analysis of Kester, 1999 23 Barlas, 1993 115 CCT but not assessing a glycopeptide (full paper was ordered as no abstract was available) Bayston, 1990 116 Not adult participants only Bell, 1990 117 Not a CCT (case series: full paper was ordered as no abstract was available) Brooks, 2002 118 Not a CCT (prospective cohort study) Bucknell, 2000 119 CCT but not assessing a glycopeptide (only MRSA high-risk patients received a glycopeptide) Cone, 2004 120 Duplicate of Mastronardi, 2004 121 Dazzi, 1994 122 Comparator not an alternative antibiotic regimen de Lalla, 2000 123 Comparator not an alternative antibiotic regimen de Lalla, 2001 124 Discussion paper (full paper was ordered as no abstract was available) De Lucas-Villarrubia, 2004 125 Not a CCT (prospective cohort study) Exner, 1992 126 Not a CCT (prospective cohort study) Ferro, 1997 127 Comparator not an alternative antibiotic regimen Feys, 1997 128 Comparator not an alternative antibiotic regimen Fontanesi, 1991 129 Discussion paper (full paper was ordered as no abstract was available) Franchelli, 1993 130 Comparator not an alternative antibiotic regimen Friberg, 1990 131 Not a CCT (case reports: full paper was ordered as no abstract was available) Gadallah, 2000 132 Not adult participants only. Primary outcome was peritonitis, SSIs were excluded from the analysis Haines, 1993 133 Letter Isringhaus, 1992 134 Not a CCT (pharmacokinetic study: all patients received same dose of glycopeptide) Karran, 1992 135 Comparator not an alternative antibiotic regimen Lazzarini, 2001 136 Not a CCT (prospective cohort) Lazzarini, 2003 137 Does not report a primary outcome (primary outcome is blood drug concentration) Mastronardi, 2004 121 Not a CCT (retrospective cohort) Mendivil Soto, 2001 138 Does not report a primary outcome Mini, 1999…”
Section: Presentation Of Resultsmentioning
confidence: 99%
“…Five summary-of-findings tables and five clinical summary tables were created corresponding to clinical sections of Plastic and Reconstructive Surgery (Breast, Cosmetic, Hand/Peripheral Nerve, Pediatric/Craniofacial, and Reconstructive sections). Of the 138 included RCTs, 18 were breast (Tables 2 and 3), 10–27 10 cosmetic (Tables 4 and 5), 28–37 21 hand/peripheral nerve (Tables 6 and 7), 38–58 61 pediatric/craniofacial (Tables 8 and 9), 16,59–118 and 41 reconstructive (Tables 10 and 11). 16,28,38–42,54–56,119–149 Forest plots are provided for all comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative and postoperative antibiotics for 1 day may decrease SSI compared with placebo, but with very low certainty (RR, 0.08; 95% CI, 0.01 to 0.57; 38 participants; one study; P = 0.01; very-low-certainty evidence). 17 Evidence: Uncertain support for preoperative and postoperative systemic antibiotics for 1 day. 16,17…”
Section: Mastectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Breast surgery is considered to be a clean surgery, and per the Centers for Disease Control and Prevention and the Surgical Care Improvement Project, antibiotic prophylaxis is recommended for a maximum of 24 hours [7]. This has been evidenced by Amland et al as well as Franchelli et al who have shown a reduction in the incidence of SSIs in autologous breast reconstruction post-mastectomy when compared to patients who did not receive any antibiotic prophylaxis [14,15]. Studies included within the quantitative assessment of this review demonstrated good comparability for underlying variables.…”
Section: Discussionmentioning
confidence: 99%